2019
DOI: 10.1002/ijch.201900040
|View full text |Cite
|
Sign up to set email alerts
|

Recent Studies on Bifunctional Perovskite Electrocatalysts in Oxygen Evolution, Oxygen Reduction, and Hydrogen Evolution Reactions under Alkaline Electrolyte

Abstract: The bifunctional electrocatalyst plays a pivotal role in renewable‐energy technologies metal‐air‐batteries and water electrolysis. The advantage of the alkaline environment allows such technologies to utilize several low‐cost and efficient non‐noble transition metal oxides. Particularly, perovskite oxides (POs) of high intrinsic catalytic activity and tunable crystal structures have shown exceptional bifunctionality characteristics in oxygen reduction reaction (ORR)/oxygen evolution reaction (OER) and hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 105 publications
(176 reference statements)
0
10
0
Order By: Relevance
“…Besides the electron transfer phenomenon, the spillover effect between Pt and SCFP in the composite is attributed as another main contributing factor to the significantly enhanced ORR and OER activities for the composite. The ORR process generally constitutes dissociative and associative pathways, the rates of which are determined by their initial oxygen dissociation energies barriers on the catalysts' surface 8a. To this end, we postulate an ORR mechanism whereby in the beginning, ORR process mainly occurs on the Pt surface where O 2 molecules are cleaved to O*.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the electron transfer phenomenon, the spillover effect between Pt and SCFP in the composite is attributed as another main contributing factor to the significantly enhanced ORR and OER activities for the composite. The ORR process generally constitutes dissociative and associative pathways, the rates of which are determined by their initial oxygen dissociation energies barriers on the catalysts' surface 8a. To this end, we postulate an ORR mechanism whereby in the beginning, ORR process mainly occurs on the Pt surface where O 2 molecules are cleaved to O*.…”
Section: Resultsmentioning
confidence: 99%
“…Since obtaining single material that can exhibit simultaneously high ORR and OER performance has been quite challenging, combining precious Pt with another low‐cost material that has high OER activity is considered an attractive alternative direction to achieve a high‐performance bifunctional electrocatalyst. Perovskite oxide with a composition formula of ABO 3 (A is rare or earth metal element while B is transition metal cation) represents one of the mostly attractive constituents . The potential of such Pt–perovskite composite has recently been demonstrated by Ciucci and co‐workers, who reported Pt 3 Ni/reduced La 0.9 Mn 0.9 Pt 0.075 Ni 0.025 O 3−δ (rLMPN) via the exsolution of Pt 3 Ni in situ on the rLMPN surface.…”
Section: Introductionmentioning
confidence: 99%
“…However, high reaction barriers and sluggish kinetics of HER, OER, and ORR lead to high energy input and low output power. [10,11] Currently, Pt and its alloys are still the most efficient electrocatalysts for acidic HER and ORR, whereas RuO 2 and IrO 2 are highly active toward acidic OER; however, the low-earth abundance, limited supply, and high costs also impede their industrial applications. [1] Notably, noble-metal-based materials with a single component typically fail to simultaneously exhibit high activity and durability for HER, ORR, and OER, especially in acidic environments.…”
mentioning
confidence: 99%
“…In this regard, the development of trifunctional SA catalysts can not only considerably reduce the use of noble metals required in electrolysis but also achieve optimized electrochemical performance. Unfortunately, most of the reported trifunctional materials are non-SA catalysts, [3,11,25,26] and they are mainly active in alkaline environments. Currently, Yao et al and Cao et al have independently suggested that Ru SA catalysts (comprising Pt-Ru-Cu [27] ) and Ru-N 4 [28] ) single sites, respectively) exhibit acidic OER performance superior or comparable to that of the state-of-the-art RuO 2 and IrO 2 .…”
mentioning
confidence: 99%
“…Recently, perovskite oxides (POs) with A 1-x A' x B y B' 1-y O z structure, where A/A' is rare-earth or alkaline-earth metal and B/B 0 is transition metal, have emerged as a potential OER catalysts. The filling degree of metal 3d antibonding orbital (e g ) in POs adjusts the spin state, the M-O bond covalence, and the shift of d-band center, further affecting the OER kinetics [59]. For example, Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ POs with an optimum e g value (1.2) has become one of the excellent OER electrocatalysts superior to IrO 2 and RuO 2 .…”
Section: Transition Metal Oxidesmentioning
confidence: 99%